Odpowiedź :
Odpowiedź:
[tex] \frac{5}{9} + \frac{1}{6} = \frac{10}{18} + \frac{3}{18} = \frac{13}{18} [/tex]
[tex]3 \frac{5}{8} + 1 \frac{7}{12} = (3 + 1) + ( \frac{5}{8} + \frac{7}{12} ) = \\ 4 + ( \frac{15}{24} + \frac{14}{24} ) = 5 \frac{5}{24} [/tex]
[tex] \frac{7}{10} - \frac{3}{8} = \frac{28}{40} - \frac{15}{40} = \frac{13}{40} [/tex]
[tex]4 \frac{1}{10} - 2 \frac{3}{4} = \frac{41}{10} - \frac{11}{4} = \frac{82}{20} - \frac{55}{20} = 1 \frac{7}{20} [/tex]
[tex]2 \frac{5}{8} - 1 \frac{1}{8} \times 1 \frac{1}{6} = \frac{21}{8} - \frac{9}{8} \times \frac{7}{6} = \frac{21}{8} - \frac{3}{2} \times \\ \frac{7}{2} = \frac{21}{8} - \frac{21}{16} = \frac{42}{16} - \frac{21}{16} = 1 \frac{5}{16} [/tex]
[tex](1 \frac{1}{4} + 2 \frac{1}{8} ) \div 1 \frac{1}{2} = ( \frac{5}{4} + \frac{17}{8} ) \times \frac{3}{2} = \\ ( \frac{10}{8} + \frac{17}{8} ) \times \frac{2}{3} = \frac{27}{8} \times \frac{2}{3} = \frac{9}{8} \times 2 = \\ 2 \frac{1}{4} [/tex]
[tex]1 \frac{1}{7} \times 5 = \frac{8}{7} \times 5 = 5 \frac{5}{7} [/tex]
[tex]1 \frac{3}{4} \times 1\frac{3}{7} = \frac{7}{4} \times \frac{10}{7} = \frac{1}{2} \times 5 = 2 \frac{1}{2} [/tex]
[tex] \frac{4}{5} \div 3 = \frac{4}{5} \times \frac{1}{3} = \frac{4}{15} [/tex]
[tex]1 \frac{3}{4} \div 3 \frac{1}{2} = \frac{7}{4} \div \frac{7}{2} = \frac{7}{4} \times \frac{2}{7} = \frac{1}{2} [/tex]